THE TRANSLATION OF RELATIVE PRONOUN â€˜YANGâ€™ IN 9 SUMMERS 10 AUTOMNS, AN INDONESIAN NOVEL: SYNTACTIC AND SEMANTIC STUDIES - Budiman, Dheni; Saifullah, Aceng Ruhendi (Apollo Project: Jurnal Ilmiah Program Studi Sastra Inggris, 2020)
The title of this research is The Translation of Relative Pronoun â€œYangâ€ in 9 summers 10 automns, an Indonesian Novel: Syntactic and Semantic Studies. This research deals with translation of the relative pronoun â€œyangâ€ in Indonesian novel. The material discussed in this research is about how the relative pronoun â€œyangâ€ is translated into English. The writer has used a descriptive-comparative method because the writer tries to explain clearly and specifically the topic on the relative pronoun â€œyangâ€, and tries to compare between the relative pronoun â€œyangâ€ and its translation in English. There are two categories in this research. The two categories are; (1) in what way the relative pronoun â€œyangâ€ explicitly is translated into English; (2) what constructions are the forms of the relative pronoun in English as the result of the translation of the relative pronoun â€œyangâ€. From the result of the research which has used corpus analysis, it can be concluded that there are three analysis of translation of the relative pronoun â€œyangâ€ after being translated into English. They are relative pronoun who, relative pronoun whom, and relative pronoun whose.